Clinical Outcome of Percutaneous Drainage for Spondylodiscitis - Murata, Yasuaki; Kanaya, Kohichi; Wada, Hiroyoshi; Wada, Keiji; Shiba, Masahiro; Hatta, Satoshi; Kato, Ken; Kato, Yoshiharu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Although vertebral debridement with interbody fusion is a useful procedure for the treatment of spondylodiscitis, anterior interbody fusion (AIF) is risky to perform on patients in a poor condition since it is highly invasive. Percutaneous nucleotomy and drainage (PND) is less invasive than AIF, but there only have been few reports regarding the outcome. The purpose of this study was to test the efficacy of PND for spondylodiscitis.Patients and Methods To analyze the effectiveness of different surgical treatments, 111 patients with spondylodiscitis were studied retrospectively. The average durations from the start of treatment until the C-reactive protein fell below 1.0 mg/dL or below the baseline value, which was defined as “recovery time” in the present study, were compared among PND, AIF, and posterior decompression.Results PND was performed when conservative treatment has been done for average 2.0 ± 0.9 months. Of the 18 PND patients, 15 (83%) showed recovery; 63 (97%) of the 65 patients who had AIF showed recovery. There was no significant difference of the mean recovery time after PND and AIF. All 10 patients whithout methicillin-resistant Staphylococcus aureus (MRSA) recovered after PND, whereas 3 of 8 patients with MRSA did not recover after PND. Of the 3 unsuccessful PND cases, 1 later had AIF, and 1 repeated PND. One patient could not undergo additional surgery because of a poor general condition.Conclusions Although the results of PND were inferior to AIF, PND is a useful next step after conservative treatment for patients in a poor condition. PND can be the initial procedure for spondylodiscitis before AIF if its limitations are understood.
Keywords: spondylodiscitis; percutaneous nucleotomy; MRSA (methicillin-resistant Staphylococcus aureus)